(2R∗,3S∗,4S∗,2″R∗,3″S∗)-Guibourtinidol-(4α→8)-catechin, a biflavanoid procyanidin of the proguibourtinidin group from Senna macranthera: its relative stereochemistry and conformation - Klika, Karel D.; Ricarte, Irvila; Trevisan, Maria Teresa Salles; de Vasconcelos Silva, Maria Goretti; Owen, Robert (Tetrahedron, 2015)
Comprehensive NMR data for the previously presumed structure of the procyanidin (2R∗,3S∗,4S∗,2″R∗,3″S∗)-guibourtinidol-(4α→8)-catechin, isolated in this case from the roots of the medicinal plant Senna macranthera, is reported. Earlier reports provided a basic plausible structure based on mass spectrometry data but lacked confirmation by NMR. Therefore the 3D structure of the compound in terms of its full relative configuration and conformational preference in CD3OD solution was established by molecular modeling using DFT in conjunction with both chemical shift, δH and δC, and NOE contact, ηH,H, NMR data.